التفسير النفسي للذكريات الباكرة - حوحو, ريان; خياط, خالد (جامعة الوادي - University of Eloued, 2016)
يعتبر مصطلح الذكريات الباكرة بسيط من خلال مفهمومه ولكنه عميق جدا لأنه يشمل الماضي والحاضر والمستقبل للفرد لذلك فالذكريات الباكرة كانت أداة أساسية مساعدة في كشف الجانب النفسي لشخصية الفرد منذ القدم حيث أخذت إهتمام العيادين منذ فترة طويلة ، فالاختلافات في استعمالاتها تتضح من خلال تفسيرات بعض العلماء وكذلك كيفية إستعمالها. كان يوجد موقفين مختلفين كبيرين لتحديد مغزى الذكريات الباكرة . موضوعنا يستعرض وجهة نظر مدرستي علم النفس الفردي والتحليل النفسي لمفهوم وتأويل الذكريات الباكرة وتوضيح الاختلافات بينهما . Abstract: The term of early recollection is simple in its definition but deeply profound in its content because it includes the past ,present ,and future of individual . so early recollection is an essential psychological tool in assessing the person’s character , that who it was widely applied by classical practianers but depeding on their theoretical background and premises , and their methodological orientation adlerian , the major methods of early recollections interpretation were individual psychology and freudien psychoanalysis. In this articale we will present both points of view and and their practical implications in the conception and interpretaion of early recollections, the refore, our problimatic to discussis.
مقال
Keywords: التفسير النفسي . منهاج العيش (أسلوب الحياة).الذكريات الباكرة . الذكريات الستائر